α-Adrenergic receptor regulation of skeletal muscle blood flow during exercise in heart failure patients with reduced ejection fraction - Barrett-O’Keefe, Zachary (Am J Physiol Regul Integr Comp Physiol, 2019)
Patients suffering from heart failure with reduced ejection fraction (HFrEF) experience impaired limb blood flow during exercise, which may be due to a disease-related increase in α-adrenergic receptor vasoconstriction. Thus, in eight patients with HFrEF (63 ± 4 yr) and eight well-matched controls (63 ± 2 yr), we examined changes in leg blood flow (Doppler ultrasound) during intra-arterial infusion of phenylephrine (PE; an α(1)-adrenergic receptor agonist) and phentolamine (Phen; a nonspecific α-adrenergic receptor antagonist) at rest and during dynamic single-leg knee-extensor exercise (0, 5, and 10 W). At rest, the PE-induced reduction in blood flow was significantly attenuated in patients with HFrEF (−15 ± 7%) compared with controls (−36 ± 5%). During exercise, the controls exhibited a blunted reduction in blood flow induced by PE (−12 ± 4, −10 ± 4, and −9 ± 2% at 0, 5, and 10 W, respectively) compared with rest, while the PE-induced change in blood flow was unchanged compared with rest in the HFrEF group (−8 ± 5, −10 ± 3, and −14 ± 3%, respectively). Phen administration increased leg blood flow to a greater extent in the HFrEF group at rest (+178 ± 34% vs. +114 ± 28%, HFrEF vs. control) and during exercise (36 ± 6, 37 ± 7, and 39 ± 6% vs. 13 ± 3, 14 ± 1, and 8 ± 3% at 0, 5, and 10 W, respectively, in HFrEF vs. control). Together, these findings imply that a HFrEF-related increase in α-adrenergic vasoconstriction restrains exercising skeletal muscle blood flow, potentially contributing to diminished exercise capacity in this population.